Superiors' Support for Work Achievement with Self Efficacy as a Mediation Variable at PT Indomarco Adi Prima Distribution Center Tangerang - Ferdi Muhammad; Anna Suzana (PT FORMOSA CENDEKIA GLOBAL, 2026)
Employee performance plays a crucial role in determining organizational effectiveness, particularly within the distribution and logistics industry where employees are required to meet demanding operational targets. This study investigates the effect of supervisor support on employee performance while examining the mediating role of self-efficacy among employees of PT Indomarco Adi Prima Distribution Center Tangerang. A quantitative research design was employed using a survey approach. Data were gathered through questionnaires administered to 130 employees selected through proportionate stratified random sampling. The collected data were analyzed using linear regression analysis and the Sobel mediation test with the assistance of SPSS software. The findings indicate that supervisor support has a significant positive impact on employee performance. Furthermore, supervisor support was found to positively influence employees’ self-efficacy, which in turn contributes significantly to improved work performance. The mediation analysis confirmed that self-efficacy serves as an intermediary mechanism through which supervisor support enhances employee performance. These findings highlight the strategic importance of supportive leadership practices in strengthening employees’ confidence and capabilities, thereby fostering sustained improvements in organizational performance.